Prevalence of human papillomavirus type 16 variants in the Federal District, Central Brazil - Cruz, Márcio R (2004)
We report the prevalence of human papillomavirus type 16 (HPV-16) variants in women with cervical lesions from the Federal District, Central Brazil. We analyzed 34 HPV-16 samples, identifying the sequence variations of E6 and L1 genes and correlating variant frequency with disease status. The most prevalent HPV-16 variant was the European (50%), followed by Asian-American (41.2%), African-1 (5.9%), and African-2 (2.9%). European and non-European variants appeared in equal frequencies among the cytological types of lesions - atypical squamous or glandular cells of undetermined significance, cytological alterations suggesting HPV infection, cervical intraepithelial neoplasias, squamous cell carcinoma, and adenocarcinoma.